Effect of titanium content on the microstructure and wear behavior of Fe(13-x)TixB7 (x=0-5) hardfacing alloy - Kılınç B.; Kocaman E.; Şen Ş.; Şen U. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this study, the effects of titanium addition on microstructure, hardness, and wear rate of Fe(13-x)TixB7 (x = 0, 1, 2, 3 and 5) based hard surface alloy layers formed by gas tungsten arc (GTA) welding method were investigated. As a result of the microstructure studies and phase analysis, it was determined that the structures of the coating layers consisted of α-Fe, αFe+Fe2B eutectic, α-Fe+Fe2Ti eutectic and hard TiB2 phases. In the hard surface alloy layer, as the amount of titanium was increased, the TiB2 phase density formed in the system increased and it was observed that rod-like and long sharpedged phases formed from the equiaxed structure. As a result of wear tests performed at different loads, it was determined that the addition of titanium reduces the wear rates in the coating layers. In addition, scanning electron microscopy (SEM) images of the worn surfaces showed that the wear mechanisms were adhesive and oxidative.